Production of biofuel by low temperature Fischer-Tropsch using Co-K/γ-Al2O3. Issue 1 (April 2020) - Makertihatha, I.G.B.N; Fadhli,; Fathoni, Zaki Al; Subagjo,
Abstract: Fischer Tropsch is a heterogeneous catalytic chemical reaction which converts a mixture of hydrogen and carbon monoxide (syngas) into a hydrocarbon product with varying chain length by polymerization reaction on the surface of the catalyst. The hydrocarbon produced from Fischer Tropsch reaction using bio-syngas is biofuel (diesel, kerosene, gasoline) that can replace petroleum-based fuels. Cobalt catalyst with potassium promoter and γ-Al2 O3 support has been successfully synthesized in Catalysis and Reaction Engineering (CaRE) laboratory, Institut Teknologi Bandung (ITB). Co-K/γ-Al2 O3 catalyst was prepared by dry impregnation method on the γ-Al2 O3 support under alkaline conditions. Catalysts were characterized using X-Ray Diffraction (XRD), temperature program reduction (TPR), and N2 physisorption measurements such as Barrett-Joyner-Halenda (BJH) and Brunauer-Emmett-Teller (BET) methods. Co-K/γ-Al2 O3 catalyst activity was evaluated using fixed bed reactor with various flow rates and temperatures which is still classified as Low-Temperature Fischer Tropsch (LTFT) process. The best results were obtained at minimum syngas flow rate and highest reaction temperature with a total pressure of 20 bar. The results show CO and H2 conversions were 96.6% and 82.31% respectively. Selectivity value of the hydrocarbon product was calculated using the Anderson Shultz Flurry (ASF) equation. The greatest selectivity value was obtained for C5+ product with selectivity value was 86.07 % wt.